A Rotation on Wiener Space with Applications. (5th August 2012) - Choi, Jae Gil; Chang, Seung Jun
Abstract : We first investigate a rotation property of Wiener measure on the product of Wiener spaces. Next, using the concept of the generalized analytic Feynman integral, we define a generalized Fourier-Feynman transform and a generalized convolution product for functionals on Wiener space. We then proceed to establish a fundamental result involving the generalized transform and the generalized convolution product.